ANALYSIS OF LAVENDER AROMATHERAPY APPLICATION TO REDUCE BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A CASE STUDY - Muhammad Al-Amin R. Sapeni; Hasriana asriana; Irawati Anwar; Suwardha Yunus; Iwan Iwan; Toshiyo Taniguch; Angela Smith Lillehei (PT.Mantaya Idea Batara, 2025)
Introduction: Hypertension is defined as a condition in which an individual has a systolic blood pressure ? 140 mmHg and a diastolic blood pressure ? 90 mmHg. Systolic blood pressure is the main measure used to diagnose hypertension. Hypertension is often referred to as a